LARGE ROOT ANGLE1, encoding OsPIN2, is involved in root system architecture in rice. (22nd December 2017) - Wang, Lingling; Guo, Mengxue; Li, Yong; Ruan, Wenyuan; Mo, Xiaorong; Wu, Zhongchang; Sturrock, Craig J; Yu, Hao; Lu, Chungui; Peng, Jinrong; Mao, Chuanzao
Abstract : OsPIN2 is identified as the casual gene responsible for the phenotype of lta1, a rice mutant that displays large root angles and a shallow root system architecture, affecting the polar transport of auxin in the root tip. Abstract: Root system architecture is very important for plant growth and crop yield. It is essential for nutrient and water uptake, anchoring, and mechanical support. Root growth angle (RGA) is a vital constituent of root system architecture and is used as a parameter for variety evaluation in plant breeding. However, little is known about the underlying molecular mechanisms that determine root growth angle in rice ( Oryza sativa ). In this study, a rice mutant large root angle1 ( lra1 ) was isolated and shown to exhibit a large RGA and reduced sensitivity to gravity. Genome resequencing and complementation assays identified OsPIN2 as the gene responsible for the mutant phenotypes. OsPIN2 was mainly expressed in roots and the base of shoots, and showed polar localization in the plasma membrane of root epidermal and cortex cells. OsPIN2 was shown to play an important role in mediating root gravitropic responses in rice and was essential for plants to produce normal RGAs. Taken together, our findings suggest that OsPIN2 plays an important role in root gravitropic responses and determining the root system architecture in rice by affecting polar auxin transport in the root tip.